National Justice Agency List, 1985 ([Verlag nicht ermittelbar], 1986)
The National Justice Agency List, 1985 is a master name and address file created and maintained by the Bureau of the Census for the Bureau of Justice Statistics. The file contains information on the following topics: prosecution and civil attorneys, public defenders, law enforcement, courts, probation and parole, juvenile corrections, local adult corrections, federal relations with American Indians, and other justice issues.